Anthocyanins Prevent AAPH-Induced Steroidogenesis Disorder in Leydig Cells by Counteracting Oxidative Stress and StAR Abnormal Expression in a Structure-Dependent Manner - Jun Hu; Xusheng Li; Naijun Wu; Cuijuan Zhu; Xinwei Jiang; Kailan Yuan; Yue Li; Jianxia Sun; Weibin Bai (MDPI AG, 2023)
Testosterone deficiency may increase the risk of sexual dysfunction and the failure of spermatogenesis. Oxidative stress that is derived from the destruction of homeostasis, disease, and exposure to contaminants can damage the steroidogenicity process in Leydig cells, resulting in a reduction in testosterone synthesis. Anthocyanins are a group of innoxious antioxidants widely recognized in food sources, and are an ideal candidate to relieve oxidative stress-related steroidogenesis disorder. However, there is still a major gap in our knowledge of the structure-function relationship of anthocyanin on the activity mentioned above. In the present study, four anthocyanins including cyanidin-3-glucoside (Cy-3-glu), delphinidin-3-glucoside (Dp-3-glu), pelargonidin-3-glucoside (Pg-3-glu), and cyanidin-3,5-diglucoside (Cy-3,5-diglu) were applied to reverse testosterone generation after employing 2,2'-Azobis(2-amidinopropane)-dihydrochloride (AAPH) as the inducer of oxidative stress in R2C cells. The results demonstrated that all four kinds of anthocyanins can inhibit ROS generation, alleviate mitochondrial membrane potential damage, and contribute to increased testosterone. Among them, Cy-3,5-diglu with diglycoside performed best on antioxidative ability and improved cell dysfunction and upregulated the expression of the steroidogenic acute regulatory protein (StAR). The molecular docking further revealed the direct combination between anthocyanins and StAR, suggesting that anthocyanins with monosaccharide were more likely to interact with StAR than with diglycoside. Taken together, these data indicate that recipient R2C cells under oxidative stress submitted to anthocyanins exhibited improved steroidogenesis in a structure-dependent manner. Anthocyanins could be considered the ideal ingredients against oxidative stress-induced testosterone deficiency.